Prevalence and associated factors of cancer pain among adult cancer patients evaluated at an oncology unit in the University of Gondar Comprehensive Specialized Hospital, northwest Ethiopia - Kibret, Anteneh Ayelign; Wolde, Haileab Fekadu; Moges, Abebe Muche; Aragie, Hailu; Teferi, Ephrem Tafesse; Assefa, Yohannes Awoke; Melese, Endalkachew Belayneh; Melesse, Mequanint; Worku, Yilkal Belete; Belay, Daniel Gashaneh; Molla, Meseret Derbew; Adugna, Dagnew Getnet (Frontiers in Pain Research, 2023)
Introduction Globally, cancer is the second leading cause of death and was responsible for 9.6 million deaths in 2018. Worldwide, 2 million people experience pain every day, and cancer pain is one of the major neglected public health problems, especially in Ethiopia. Despite reporting the burden and risk factors of cancer pain as a principal importance, there are limited studies. Therefore, this study aimed to assess the prevalence of cancer pain and its associated factors among adult patients evaluated at the oncology ward in the University of Gondar Comprehensive Specialized Hospital, northwest Ethiopia. Methods An institution-based cross-sectional study was conducted from 1 January to 31 March 2021. A systematic random sampling technique was used to select the total sample size of 384 patients. Data were collected using pretested and structured interviewer-administered questionnaire. Bivariate and multivariate logistic regression models were fitted to identify the factors associated with cancer pain among patients with cancer. An adjusted odds ratio (AOR) with a 95% CI was computed to determine the level of significance. Results A total of 384 study participants were involved, with a response rate of 97.5%. The proportion of cancer pain was found to be 59.9% (95% CI 54.8–64.8). The odds of cancer pain were escalated by anxiety (AOR = 2.52, 95% CI 1.02–6.19), patients with hematological cancer (AOR = 4.68, 95% CI 1.30–16.74), gastrointestinal cancer (AOR = 5.15, 95% CI 1.45–18.2), and stages III and IV (AOR = 14.3, 95% CI 3.20–63.7). Conclusion The prevalence of cancer pain among adult patients with cancer in northwest Ethiopia is relatively high. Variables such as anxiety, types of cancer, and stage of cancer had a statistically significant association with cancer pain. Hence, to advance the management of pain, it is better to create more awareness regarding cancer-related pain and provide palliative care early on in the diagnosis of the disease.